Urban Adolescents’ Physical Activity Experience, Physical Activity Levels, and Use of Screen-Based Media during Leisure Time: A Structural Model - Xie, Hui; Scott, Jason L.; Caldwell, Linda L. (Frontiers in Psychology, 2018)
There is limited understanding of the relationship between physical activity and use of screen-based media, two important behaviors associated with adolescents’ health outcomes. To understand this relationship, researchers may need to consider not only physical activity level but also physical activity experience (i.e., affective experience obtained from doing physical activity). Using a sample predominantly consisting of African and Latino American urban adolescents, this study examined the interrelationships between physical activity experience, physical activity level, and use of screen-based media during leisure time. Data collected using self-report, paper and pencil surveys was analyzed using structural equation modeling. Results showed that physical activity experience was positively associated with physical activity level and had a direct negative relationship with use of non-active video games for males and a direct negative relationship with use of computer/Internet for both genders, after controlling for physical activity level. Physical activity level did not have a direct relationship with use of non-active video games or computer/Internet. However, physical activity level had a direct negative association with use of TV/movies. This study suggests that physical activity experience may play an important role in promoting physical activity and thwarting use of screen-based media among adolescents.